PENGGUNAAN MEDIA VIDEO UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATERI BIOSFER PADA SISWA KELAS XI IPSMAN 2 PONTIANAK TAHUN PELAJARAN 2015/2016 - - - Rina (Media Komunikasi Geografi, 2016)
The purposes of this study are To increase motivation to learn and learning outcome geography in class XI IPS 1 MAN 2 Pontianak in the academic year of 2015/2016 in geography subject.The method of the study used in this research is a classroom action research with some stages called: planning, action, observation, and reflection. The stages are arranged to form a cycle. This research is collaborative study which involves colleagues who collaborate to identify the problems, preparation of plans, carrying out the action, observation and reflection. The Subjects of this study is class XI IPS 1 MAN 2 Pontianak consist of 40 students. Techniques of data collection used are, Questionnaire of motivation to learn, Test; and Observation, Analysis of the data used is quantitative analysis. The Results of this study are: students’ motivation to learn geography and geography learning outcomes in the initial conditions of 32 students or 80% who have not yet reached KKM and 8 students or 20% who had reached KKM for motivation to learn geography. There are 28 geography student learning outcomes or 70% who have not yet reached KKM and 12 students or 30% has been reached KKM. In the first cycle there are    23 students or 57.5% who have not yet reached KKM and 17 or 42.5% of students who have achieved learning outcomes geography KKM. Besides, there are 21 students or 52.5% have not yet reached KKM and 19 students or 47.5 % has reached KKM. In the second cycle there are 7 or 17.5% of students who have not yet reached KKM and 33 or 82.5% of students who have reached KKM. Besides, there are  6 student of geography learning outcomes or 15% has not been reached KKM and 34 students or 85% has been reached KKM . Keywords: Media Video, Motivation and Geography Learning Outcomes, Biosphere